STRATEGI HUMAS DALAM PENJARINGAN CALON SISWA BARU TAHUN AJARAN 2013 – 2014 DI SMK WACHID HASYIM SURABAYA - EVENDY, NOVAN (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2014)
ABSTRACTThe research was conducted using qualitative approach and using the method of observation, interview and documentation to collect the data. Where the subject matter of the interview conducted is some people related to public relations. And that became the object of this research is a public relations strategy in SMK Wachid Hasyim Surabaya. After the data is retrieved, the data analysis process done through qualitative analysis techniques. After all the process of data collection and data analysis is complete, test the validity of the data was undertaken. Among them are the extension of participation, persistence observations, triangulation, and member check. In order for later data obtained can be accounted for truth and its validity. The results of the study showed that the SMK Wachid Hasyim Surabaya has yet to implement the strategy and using the right medium for school. Which strategies and media used, have not been analysed in advance using a SWOT analysis, and strategy are also not yet adapted to the vision and mission of the school. SMK Wachid Hasyim Surabaya are still using the old strategy that he believes can be effective to attract new prospective students.Key words: Public Relations, Media Strategy, Prospective Students